2021
DOI: 10.5435/jaaos-d-20-01089
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities and Incidence of Postoperative Complications in Obese Patients Undergoing Total Knee Arthroplasty: Analysis of the American College of Surgeons National Surgical Quality Improvement Program Data Set

Abstract: Introduction: Total knee arthroplasty (TKA) is common but complex operation. A paucity of literature exists on differences between Hispanics and non-Hispanics with TKA. Our study aims to investigate the association between Hispanic ethnicity and complications in obese patients undergoing TKA.Methods: This is a retrospective cohort study using the National Surgical Quality Improvement Program database for patients with body mass index $30 kg/m 2 who underwent TKA. Exposure in this study was ethnicity (Hispanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…15–17 Although medical and surgical management are important for care, recent evidence suggests that a person's socioeconomic factors impact outcomes and must be taken into account to optimize care. 7,8,13,18–20 The present study found that patients with educational deficiencies had increased rates of readmission and major complications compared with those without disparities following hip and ankle fracture management. Moreover, economic disparities were associated with an increased risk of readmission and revision following hip fixation and infection and readmission following ankle fracture surgery.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…15–17 Although medical and surgical management are important for care, recent evidence suggests that a person's socioeconomic factors impact outcomes and must be taken into account to optimize care. 7,8,13,18–20 The present study found that patients with educational deficiencies had increased rates of readmission and major complications compared with those without disparities following hip and ankle fracture management. Moreover, economic disparities were associated with an increased risk of readmission and revision following hip fixation and infection and readmission following ankle fracture surgery.…”
Section: Discussionmentioning
confidence: 49%
“…Previous literature has identified various factors of SDH associated with poor outcomes, such as race, insurance status, poor finances, and inadequate literacy, among others. 7,8,13,[18][19][20] Rubenstein et al 18 found that black race significantly negatively correlated with knee functional outcome when compared with white race following total joint arthroplasty. Education, gender, comorbidities, and neighborhood poverty were also found to be significantly associated with lower functional outcomes.…”
Section: Discussionmentioning
confidence: 99%